Patient satisfaction in an observation unit: the Consumer Assessment of Health Providers and Systems Hospital Survey. Issue 8 (22nd July 2009) - Ng, C W L; Lim, G H; McMaster, F; Molina, J; Seow, E; Heng, B H
Abstract : Background: The growing demand for inpatient beds in Singapore has led Tan Tock Seng Hospital to set up an observation medicine unit where patients are monitored and discharged within a 24-h period. Methods: Using the Consumer Assessment of Health Providers and Systems (CAHPS) Hospital Survey, this descriptive study examines the satisfaction levels of patients admitted into an observation unit, in particular the communication between patients and doctors and nurses. The anonymous surveys were either self-administered by the patients or by the research assistant or nurses. Results: 271 patients completed the survey, with 96% of patients satisfied with the politeness (ie, treating them with courtesy and respect, listening carefully to them) of the medical staff. More highly educated patients were more satisfied with the communication between the doctors or nurses, compared with less educated patients (p<0.05). However, less educated patients gave a higher rating of their observation unit stay than more educated patients (p<0.05). Conclusion: With patient satisfaction becoming increasingly important as an indicator of the quality of care in the present healthcare environment, doctors and nurses should seek to improve their communication with their patients so as to ensure that patients are satisfied and receive quality care.